Stakeholder Analysis in The Development of Natural Silk Agribusiness in South Sulawesi Province - Ashar, Nurul Magfirah; Nurmalina, Rita; Muflikh, Yanti Nuraeni (International Journal of Agriculture System, 2024)
Natural silk is an agribusiness activity that consists of a whole series of interconnected and interrelated upstream to downstream sub-systems. The government has intensified the natural silk development policy program in South Sulawesi Province through the regional superior industrial development plan. As a form of superior industrial development as stipulated in the 2018-2038 South Sulawesi Provincial Industrial Development Plan, the involvement of several stakeholders. This research aims to find out all stakeholders involved in policy-making and decision-making in the agricultural and industrial sectors, which are directly related to the development of natural silk agribusiness in South Sulawesi Province. This research was located in South Sulawesi Province, with a regional focus on Soppeng Regency and Wajo Regency, and was carried out for three months, namely February – April 2024. The data obtained was analyzed using the analytical method stakeholder, which was done to interpret interest and influence. Twenty-four stakeholders are involved in developing natural silk agribusiness in South Sulawesi Province. Mapping stakeholders based on importance and influence makes eight stakeholders in quadrants subject (high interest but low influence), five stakeholders in quadrants as key players (high influence and high importance), ten stakeholders in quadrants context setter (high influence but low interest), and one stakeholder in quadrants crowd (low influence and low interest). Stakeholders must coordinate and synergize effectively, establishing good cooperation for the continued development of natural silk agribusiness in South Sulawesi Province in the future. The relationships between stakeholders in the natural silk development policy program in South Sulawesi Province consist of (1) communication, (2) coordination, and (3) cooperation.